Hubungan antara Perilaku Makan dan Aktivitas Fisik dengan Komposisi Tubuh pada Siswa Sekolah Menengah - Lewa, Shintya Clara Paiding; Amani, Patwa (Poltekkes Kemenkes Palembang, 2024)
Background: Body composition is part of body fat and non-fat tissue, measured as percentage of a person's body weight. Body composition is essential as a health parameter. Various factors influence body composition. In middle school-age teenagers with busy academic activities and unhealthy eating behavior, body composition becomes a problem not only for health but also aesthetics, which will ultimately affect a teenager's level of self-confidence. This study aims to evaluate the relationship between eating behavior and physical activity with body composition in high school-age adolescents. Methods: This was an observational study with a cross-sectional design. The subjects were 93 male and female students aged 16-18 years at State High School 95 Jakarta. Sampling was taken using the Cluster Simple Random Sampling technique. Physical activity was measured using the International Physical Activity Questionnaires (IPAQ), eating behavior was evaluated using the Food Preference Questionnaire (FPQ) and body composition was assessed using Bioelectrical Impedance Analysis (BIA). Results: There is a significant relationship between eating behavior and visceral fat (p= 0.001), total fat (p= 0.004), muscle mass (p= 0.014). There was no significant relationship between physical activity and body composition, namely visceral fat (p= 0.132), total fat (p= 0.755), muscle mass (p= 0.072). Conclusion: Eating behavior is significantly related to body composition in high school age adolescents, but not to physical activity. Keywords : Eating behavior, physical activity, body composition.